If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -5m = 45 Solving 20 + -5m = 45 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -5m = 45 + -20 Combine like terms: 20 + -20 = 0 0 + -5m = 45 + -20 -5m = 45 + -20 Combine like terms: 45 + -20 = 25 -5m = 25 Divide each side by '-5'. m = -5 Simplifying m = -5
| -6a-(4b-12a+7c)= | | 2(2+3x)+2(2x-1)=3(x+6) | | 729=0 | | 7x+37=149 | | 5c+4=(-26) | | 9t+17=-1 | | 8t-9+4t=59-5t | | x+7=31 | | (x+14)+(3x-18)=180 | | (9x+2)+(2x)=90 | | 7(7-1*1)=42 | | 9(7t+6)=306 | | 15-10t+7+8t= | | -4(x+3)(x+3)+5=-8 | | 7x-7x-1=42 | | 68-5= | | x^2+19x+29=5x-4 | | x^2+4x=-7 | | x^2+2x-34=1 | | (13-b)4=(2-0.5b)6 | | x-24.3=-6 | | -12=4m+8 | | 4t+22=90 | | 3z+2=(z-3)+9 | | (x-3)(-15)= | | 9m-3(2m-3)=11 | | -(67r+67s-94)= | | 2x+8=-24 | | 5+14-2w=9-(4w+2) | | 45+0.20m=66 | | 11x-4=56-x | | 25.24=5x+3.89 |